Les spots politiques télévisés britanniques : de l’anecdote télévisuelle à la mémoire collective - David Haigron (Revue LISA)
At the beginning of the 1950s the Party Election and Political Broadcasts (PEBs and PPBs) first started as a mere anecdote. They are now the parties’ major medium to address the voters directly and political communication has entered a “television era”. As a matter of fact, this evolution implies certain consequences and constitutes a new step in the chronology of Britain’s political history. The first expression of this evolution is a shift of the space of political representation towards television. In this respect, PEBs and PPBs can be regarded as a prism through which it is possible to assess the different histories that they are part of, i.e. that of the British media , that of political communication and that of society and its changes. Yet Party Broadcasts have a bipolar relation to History. On the one hand, their message is meant to be circumstantial and linked to an election. On the other, their linguistic and iconic discourse aims at leaving a lasting print in collective memory.